Blood Transfusion Associated Diseases and Complications in Thalassaemia Patients - Tayyab, Muhammad (Europasian Journal of Medical Sciences, 2020)
Background: Transfusion Transmitted Infections (TTIs) are going to hit as a major risk factor in overpopulated regions of the world comprising thalassaemia as a main concern. The variety of infectious diseases that transfer from blood donors to thalassaemia patients leading complications which result in delay hemolytic transfusion reactions and different types of infections whose causative agents may be HBV, HCV, HIV and Syphilis etc. Epidemiology: The thalassaemia affects almost 4.4 of every 10000 births worldwide although its rate in Pakistan is 5000 to 10000 births per year with 5-7 % estimated carrier rate. The blood transfusion and transmissible infections ratio in low income countries is as, HIV presence is from 0.33% to 1.66%, HBV presence is from 2.00% to 4.50%, HCV presence is from 0.50% to2.23% and Syphilis presence is from 0.60% to 1.81%. Diagnostics: The Immuno-chromatographic tests are affordable and can be valid to be used for blood screening throughout world. Blood samples should be processed for a counter check via ELISA/ CLIA and NAT technique to eliminate risk of HBV, HCV, HIV and syphilis deadly infections. Treatment: Patients must be provided regular blood transfusion to keep average hemoglobin level at 10-12 g/dl. Other treatments include Iron Chelation therapy which is mandatory for better life expectancy as well as splenectomy, stem cell transplant and gene therapy. Conclusion: The blood transfusion infections based on ICT (Immuno-chromatographic technique) prove unreliable while CLIA (ChemiluminescenceImmunoassay) is reliable comparatively due to capturing weak positive and low titer infectious agents. In order to avoid the delayed hemolytic transfusion reactions it is enforced to detect the subgroups of blood like A (A1 and A2) and AB (A1B and A2B).